Design and Full-Scale Testing of Low-Cost Texas Department of Transportation Type T631 Bridge Rail for MASH Test Level 2 and 3 Applications. Issue 1 (January 2015) - Williams, William F.; Bligh, Roger; Odell, Wade; Smith, Amy; Holt, John
The purpose of this project was to design and test a low-cost bridge rail system that would be compatible with the Midwest Guardrail System (31 in. height) and minimized or eliminated deck damage when impacted by errant vehicles. The Texas Type T631 bridge rail developed for this project is a flexible, low-cost bridge rail system for Test Level 2 (TL-2) applications. The Texas Department of Transportation Type T631 bridge rail designed and developed for this project was evaluated under Manual for Assessing Safety Hardware (MASH) TL-2 in 2013. The bridge rail incorporated S3X5.7 steel sections designed to yield at the post baseplate. The post baseplate was designed to distribute the baseplate bearing and shear forces without causing damage to the 8-in.-thick reinforced concrete deck. The welds on the posts were designed such that the post yielded without tearing away from the top of the baseplate. The rail element consisted of a 12-gauge W-beam rail element. The rail element was attached to the post with a bolt of diameter 5/16 in. This bolt was designed to break away without adversely affecting vehicle performance. The posts were spaced 6 ft 3 in. on centers for TL-2. The post spacing was reduced to 3 ft 1½ in. on centers and evaluated for MASH Test Level 3 (TL-3) specifications in 2014. At the smaller post spacing, the T631 met all the performance requirements of MASH TL-3. Details of the design and testing of the T631 for MASH TL-2 and MASH TL-3 specifications are provided in this paper.